The Use of Cloze Test To Test Reading Comprehension of Non-English Department Students - Sukarni, Sri (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
This research aimed to describe the result of the non-English department studentsâ€™ reading comprehension tested by using cloze test and the effect of using cloze test on non-English department studentsâ€™ achievement on reading comprehension. This research is classified into pre-experimental research that used one group pre-test and post-test design.Â The population of this research is the non-English department students in the academic Year 2020/2021 with a total number of 107 students. The researcher used non-probability sampling type purposive sampling technique and there were 44 students taken as samples. The test is the instrument in this research. Data are taken from the result of pre-test and post-test then analyzed by using statistical technique. The analysis is used to find the significant difference in the studentsâ€™ reading comprehension ability before and after the use of cloze test. In this research, the researcher used paired sample t-test through SPSS 17.0 to analyze the data. Based on data analysis, the mean score of the pre-test was 46.86 categorized as poor whereas the mean score of the post-test was 65.61 categorized as average to good. The mean score of the pre-test 46.86 smaller than 65.61 mean scores of the post-test. It meant that there was a difference mean score of studentsâ€™ reading comprehension between the pre-test and post-test. This finding showed there was a different score before and after giving treatment. The result of paired samples t-test analysis showed the significance value Sig. (2-tailed) < alpha (0.000 < 0.05). Therefore, the alternative hypotheses which stated that there is an effect of using cloze test on improving non-English department studentsâ€™ reading comprehension is accepted. It is concluded that there was an effect of cloze test on improving non-English department studentsâ€™ reading comprehension.